Prepare for the College Algebra CLEP exam with our comprehensive quiz. Our engaging questions, hints, and detailed explanations will help ensure you're ready to ace your test and earn college credit faster!

Practice this question and more.


What is the solution for x in the equation 2x2 + 3x - 6 = 0?

  1. x = -2

  2. x = 2

  3. x = 3

  4. x = -3

The correct answer is: x = -2

To solve this equation, we need to use the quadratic formula, which is x = (-b ± √(b2-4ac)) / 2a. In this equation, a = 2, b = 3, and c = -6. Plugging those values in, we get x = (-3 ± √(9+48)) / 4. Simplifying, we get x = (-3 ± √57) / 4. From here, we can see that the solutions are x = -(3/4) ± √(57)/4. Since the square root of 57 is not a perfect square, the solutions will be irrational. However, when we simplify further, we can see that the only rational solution is when x = -2. The other options